Reproducibility of the rotor 2INpower crankset for monitoring cycling power output: a comprehensive analysis in different real-context situations - Rodríguez-Rielves, V.; Martínez-Cava, A.; Buendía-Romero, A.; Lillo-Beviá, J. R.; Courel-Ibanez, J.; Hernández-Belmonte, A.; Pallarés, J. G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To examine the reproducibility (intradevice and interdevice agreement) of the Rotor 2INpower device under a wide range of cycling conditions.